Designing Of Pulse Phase-Locked Loops - A. A. Deryushev; I. L. Svito; M. S. Shmakov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers pulse phase-locked loops (PPLL) in which switching of structure and parameters is used for improvement of dynamic and spectral characteristics Classification of existing switching algorithms is given in the paper. The paper proposes designing methodology that takes into account discrete and non-linear characteristics of the considered devices, and also requirements to synchronism, stability, speed, spectral characteristics, peculiarities of various switching algorithms. Practical approbation of the methodology has been carried out.